ANALISIS KOMPARATIF HASIL BELAJAR BAHASA INDONESIA BERBASIS KURIKULUM MERDEKA PADA PEMBELAJARAN DARING DAN LURING - Ika Shinthya Yusriana; Machrus Abadi (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Comparative Analysis of Indonesian Language Learning Outcomes Based on the Independent Curriculum in Online and Offline Learning. This study aims to describe the comparison of the learning outcomes of Indonesian language based on the independent curriculum on brave and attractive learning for class X students majoring in Computer Network Engineering  at SMK Negeri 11 Malang. This study is both research and quantitative. Data was collected using a learning achievement test and then analyzed using descriptive statistics. The results showed that the learning outcomes of students with the offline learning system were superior to those of students with the online learning system.